Propolis: Traditional uses, Phytochemical Composition and Pharmacological Properties - Khamsah Suryati, Mohd; Nor Elani, Mat Nafi; Ammira Shafiqha, Abdul Khadar; Ainur Awanis, Mohd Badiazaman (2018)
Propolis is a sticky material manufactured by bees to build and protect their hive. Propolis had been used worldwide for years in folk medicine. The aim of this paper is to give information about traditional uses, phytochemical screening and pharmacological studies of propolis in the world by using secondary references such as journals and articles. The traditional uses of propolis include home remedies, toothpastes, mouthwashes, creams, drops, dietary supplement, anti-putrefactive, anti-pyretic agent, antiseptic, wound healing agent, tuberculosis treatment, cold syndrome, treatment of burns, acne, herpes simplex and genitalis, neurodermatitis, anti-fungal activities in ocular and vaginal infections. Phytochemical screening had shown that propolis contains anthraquinones, alkaloids, fatty acids, flavonoids, glycosides, saponins, triterpenes, tannins and volatile oils. Propolis has pharmacological activities such as anti-inflammatory, antibacterial, antitumor, antioxidant and anti-cancer. Based on this article, propolis has many function and can be used in future as an alternative medicine.